2008
DOI: 10.1176/appi.ps.59.4.377
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cost Sharing on Antidepressant Use Among Older Adults in British Columbia

Abstract: Objective-Antidepressant therapies are underused among older adults and could be further curtailed by patient cost-sharing requirements. The authors studied the effects of two sequential costsharing policies in a large, stable population of all British Columbia seniors: change from full prescription coverage to $10-$25 copayments (copay) in January 2002 and replacement with incomebased deductibles and 25% coinsurance in May 2003.Methods-PharmaNet data were used to calculate monthly dispensing of antidepressant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Grootendorst (2001) analysed the impact of referenced -based pricing on nitrates usage and cost reduction by using also the cost per milligram. Similar approach was found useful in case of comparison of the medicines prices for particular therapeutic groups (Wang 2008) , which is also the case in our study. …”
Section: Introductionsupporting
confidence: 73%
“…Grootendorst (2001) analysed the impact of referenced -based pricing on nitrates usage and cost reduction by using also the cost per milligram. Similar approach was found useful in case of comparison of the medicines prices for particular therapeutic groups (Wang 2008) , which is also the case in our study. …”
Section: Introductionsupporting
confidence: 73%
“…8. Evidence of such anticipatory prescribing behavior or ''stockpiling'' can be found in the literature (Marshall et al 2002;Wang et al 2008).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…finally, we discuss an intervention that is feasible and represents an innovative approach to improving health outcomes. Several studies have examined the impact of cost-sharing on prescription drug adherence within government-funded pharmaceutical programs in Canada (Tamblyn et al 2001;Li et al 2007;Anis et al 2005;Wang et al 2008;Schneeweiss et al 2007a,b), and at least one study has examined the impact of cost-sharing for patients who have private drug insurance (ungar et al 2008). Even with relatively small copayments, all these studies have found that cost-sharing significantly reduces adherence even after myocardial infarction (Schneeweiss et al 2007a,b).…”
Section: Strengths and Limitationsmentioning
confidence: 99%